Facilities and Infrastructure Management - Ilmi, Irpan; Erihadiana, Mohamad; Wanayati, Sri (EDUTEC : Journal of Education And Technology, 2023)
Educational facilities and infrastructure are supporting tools in achieving learning objectives. MI Al Washliyah Cirebon is an A-accredited school that has quite complete facilities, such as classrooms, mosques, cooperatives, teachers' offices, UKS rooms, cooperatives and others. This study aims to determine the management of facilities and infrastructure (Strategy for the procurement of infrastructure at MI Al Washliyah Cirebon). This research uses descriptive qualitative research method. Data processing: triangulation (combined), data analysis is inductive/qualitative. Data Source: Principal, Deputy Principal for facilities and infrastructure Sector. Data collection techniques: observation, interviews, documentation. Research instruments: researchers, observation instruments, interview instruments. Results of the research and analysis show that the facilities and infrastructure education at MI Al Washliyah Cirebon has been planned effectively through the following stages: (i) collecting data on educational facilities and infrastructure which includes parties who understand the educational needs. Facilities and infrastructure at MI Al Washliyah Cirebon (ii) requesting a list submission infrastructure needs of each teacher, homeroom teacher and parents through the committee, (iii) needs analysis in infrastructure planning. Procurement procedures through: (i) procurement, (ii) acceptance of grants and assistance, (iii) maintenance (iv) purchases. Evaluation of educational facilities carried out at MI Al Washliyah Cirebon is effective, carried out continuously, comprehensively and objectively including: short term (1 year), medium term (5 years), long term (10 years).